2014
DOI: 10.1371/journal.pone.0100200
|View full text |Cite
|
Sign up to set email alerts
|

Di-Tyrosine Cross-Link Decreases the Collisional Cross-Section of Aβ Peptide Dimers and Trimers in the Gas Phase: An Ion Mobility Study

Abstract: Oligomeric forms of Aβ peptide are most likely the main synaptotoxic and neurotoxic agent in Alzheimer’s disease. Toxicity of various Aβ oligomeric forms has been confirmed in vivo and also in vitro. However, in vitro preparations were found to be orders of magnitude less toxic than oligomers obtained from in vivo sources. This difference can be explained by the presence of a covalent cross-link, which would stabilize the oligomer. In the present work, we have characterized the structural properties of Aβ dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 64 publications
7
28
0
Order By: Relevance
“…[43][44][45][46][47] Also our ensemble reveals the existence of off-pathway configurations with mixed αβ or all α contents, which have already been discussed in atomistic REMD-OPLS simulations of the Aβ1-42 dimer 28 and a NMR-guided metadynamics simulation of the Aβ1-40 monomer. 48 The finding of compact and extended dimer configurations with small and large end-to-end distances of the peptides is also consistent with recent IM-MS analysis of Aβ1-40 oligomers, 9,37 and all-atom simulations of the Aβ1-28 and Aβ1-40 monomers in explicit solvent. 17,48 Recent experiments and simulations have emphasized the role of the Nterminus in self-assembly.…”
Section: Discussionsupporting
confidence: 86%
“…[43][44][45][46][47] Also our ensemble reveals the existence of off-pathway configurations with mixed αβ or all α contents, which have already been discussed in atomistic REMD-OPLS simulations of the Aβ1-42 dimer 28 and a NMR-guided metadynamics simulation of the Aβ1-40 monomer. 48 The finding of compact and extended dimer configurations with small and large end-to-end distances of the peptides is also consistent with recent IM-MS analysis of Aβ1-40 oligomers, 9,37 and all-atom simulations of the Aβ1-28 and Aβ1-40 monomers in explicit solvent. 17,48 Recent experiments and simulations have emphasized the role of the Nterminus in self-assembly.…”
Section: Discussionsupporting
confidence: 86%
“…Instead, it stabilises or traps Aβ assemblies and delay further elongation. This is supported by previous reports that showed that DiY cross-linked Aβ are slow to fibrilise and form long-lived soluble oligomeric aggregates [19][20][21][22] . Mass-spectrometry studies have revealed that DiY cross-linking leads to the stabilisation of Aβ40 in compact oligomeric species 22 , which is in strong support of our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Cu 2+ /H202) (MCO) and peroxidase-catalysed oxidation. Some studies have shown that DiY cross-linking of both Ab40 and Ab42 results in the generation of toxic Ab assemblies with reduced assembly speed [17][18][19][20][21][22] , inhibit Ab40 assembly, especially in highly oxidative environments 23 or induce the formation of Ab42 non-amyloidogenic aggregates when catalysed with a high concentration of Cu 2+ 24 . Whether DiY cross-linking is a driver, facilitator or inhibitor of Ab self-assembly is still not clear from these studies.…”
Section: Introductionmentioning
confidence: 99%
“…) others have observed SDS stable oligomeric species were not artificially induced by SDS (Sitkiewicz et al . ). Our results support the latter observation based on our own control experiments, mass spectral data analysis and cell binding analysis following treatment with oligomeric Aβ species.…”
Section: Discussionmentioning
confidence: 97%